Association between post-game recovery protocols, physical and perceived recovery, and performance in elite Australian Football League players - Bahnert, A.; Norton, K.; Lock, P. (Journal of Science and Medicine in Sport, 2013)
Objectives To determine the associations between post-game recovery protocols and physical and perceptual recovery, and game performance in Australian Football League players. Design